2013
DOI: 10.1590/s0102-86502013000200008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copaiba oil on correction of abdominal wall defect treated with the use of polypropylene/polyglecaprone mesh

Abstract: PURPOSE:To evaluate the effects of copaiba oil on the correction of abdominal defect treated with the use of polypropylene/ polyglecaprone mesh in rats. METHODS:A defect in the abdominal wall was created and corrected with polypropylene/polyglecaprone mesh in 36 rats. They were randomly distributed into three groups: control, copaiba by oral administration (gavage) and copaiba oil dip in the mesh. Euthanasia was performed after seven, 14 and 21 post-operative days. The healing process was analyzed regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 15 publications
0
24
1
2
Order By: Relevance
“…Its presence on the osteoclast precursors and mature osteoclasts´ surface plays an important role in promoting the differentiation and activation of osteoclasts, leading to bone resorption 11,12,20 . Silva et al 20 believe that positive influence of copaiba oil on alveolar bone formation is probably explained by the fact that the sesquiterpenes of copaiba oil inhibited the action of RANK, facilitating the alveolar bone repair.…”
Section: Discussionmentioning
confidence: 99%
“…Its presence on the osteoclast precursors and mature osteoclasts´ surface plays an important role in promoting the differentiation and activation of osteoclasts, leading to bone resorption 11,12,20 . Silva et al 20 believe that positive influence of copaiba oil on alveolar bone formation is probably explained by the fact that the sesquiterpenes of copaiba oil inhibited the action of RANK, facilitating the alveolar bone repair.…”
Section: Discussionmentioning
confidence: 99%
“…Copaiba oil has been used by several authors to test its anti-inflammatory and antimicrobial effects [17][18][19] , and the results have shown that the main active components responsible for these properties are the diterpenes and sesquiterpenes, as bisabolol and beta betacariofileno 9 . Knowing that the copaiba used in this study does not show effects against gram-negative bacteria 13 and that the model of CLP primarily deflagrates gramnegative septicemia, it is believed that the determining factor for increasing animal survival was the anti-inflammatory action of this plant, by modulating the inflammatory response and subsequent issue damage mediated by free radicals and proinflammatory citocinais against sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Copaiba oil administered seven days before and therapeutically liver damage from paracetamol showed hepatoprotective effects, however, was only analyzed the effects within 24 hours after injury, thus, further studies should be conducted to understand whether longer periods in the oil copaiba can cause harm liver, as well as studies to identify the active principle and / or how this oil works to reduce liver damage 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Copaiba oil stands out among the Amazonia`s medicinal plants due to be attributed to this an important anti-inflamatory effect 17,18 and a function that promotes protection in the liver tissue 19 .…”
Section: Introductionmentioning
confidence: 99%